Investasi pada pasar modal syariah - Huda, Nurul; Nasution, Mustafa Edwin (Rawamangun, Jakarta : Kencana Prenada Media Group, 2007)
Investment in the Islamic capital market in Indonesia
Includes bibliographical references (p. [173]-177)
Keywords: Capital market -- Indonesia; Investments -- Indonesia; Islam -- Economic aspects -- Indonesia